Short Term Load Forecasting using Functional Link Network - Muthukumaran, Sithambaram; Thyagarajah, K.; Paulraj, Murugesa Pandiyan, Prof. Madya Dr. (EuroJournals Publishing, 2011)
Link to publisher's homepage at http://www.eurojournals.com/